Psychoeducation on Improving Mental Health Literacy and Adjustment to Illness in Patients With Type 2 Diabetes: An Experimental Stud - Alireza Karimpour Vazifehkhorani; Mansoureh Karimzadeh; Mohsen Poursadeghiyan; Fatemeh Rahmati-Najarkolaei (Iranian Rehabilitation Journal, 2018)
Objectives: The present study investigated the role of psychoeducation in improving mental health literacy and adaptation in patients with type 2 diabetes. Methods: The present study was an interventional study with pre-test, post-test and follow-up design with a control group. The study population included patients with type 2 diabetes who referred to Iran Hospital. Based on the research method and considering the missing data, a sample size of 80 people was considered. In total, 40 patients were selected as the intervention group and 40 subjects as the controls by purposeful sampling method. The subjects were randomly assigned into the two groups. The obtained data were collected by O’Connere and Casey’s mental health literacy questionnaire and psychosocial compatibility questionnaire of Moro and colleagues. The purpose of psychological education in this study, which was used as the intervention, was Cognitive Behavioral Therapy (CBT). Training was performed in a group format. Therapeutic sessions were 11 one-hour sessions. Results: The obtained results suggested that the effect of intervention in the  post-test phase was 57% on mental health literacy and 48% in follow-up. In addition, the effect of intervention on adjustment in the post-test phase was 39%, and in the follow-up phase 38%. Discussion: Psychological trainings like CBT can predict the information that is more important in diabetes self-management. Increasing the mental health literacy rate for psychiatric disorders associated with type 2 diabetes, improves compatibility, which will improve the quality of life and lifestyle of people with type 2 diabetes.